TEACHERS’ CHALLENGES REGARDING ONLINE MODALITY OF TEACHING - Camacho, sairah mae; Butac, Susan (International Journal of Arts, Sciences and Education, 2022)
Online teaching, as the trend of the New Normal, is highly dependent on the power of digital platforms. Technology and related interrelated factors affect teachers’ abilities and performances. This study aims to describe the challenges and difficulties experienced by teachers, especially the Physical education ones, in teaching their courses online. The quantitative method was the approach taken for this particular study. In particular, the Descriptive survey was applied in this study. For this study, the researchers chose the quantitative research approach because it is the one that places the most emphasis on quantitative data. Probability Simple Random sampling was used in selecting the participants of this study. Specifically, this research encompasses the online teaching challenges of PE teachers of all branches of New Era University in Quezon City, Batangas, Rizal, and Pampanga. The conclusion claims that teachers highly experienced insufficient time in online teaching and discharging their responsibilities to their students, who are also paralyzed by the absence of technology in performing their academics. Thus, technology hinders them from performing better. This result was revealed. It is proposed that retooling, such as training and seminars, should be granted to teachers and students to enable them to combat the challenges of online modular learning—Internet provisions from the institution or government should empower this.